(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Plexiform fibromyxoma is a rare mesenchymal tumor of the stomach that was first included in the World Health Organization classification of digestive system tumors in 2010. The tumor commonly occurs in the gastric antrum and pylorus and is frequently misdiagnosed as gastrointestinal stromal tumor (GIST) because of its nonspecific clinical, endoscopic, and radiologic features. Case presentation: A 66-year-old woman was admitted to the hospital with upper gastrointestinal bleeding and persistent dull abdominal pain. Upper gastrointestinal endoscopy revealed a polypoid lesion causing pyloric stenosis. The patient underwent distal gastrectomy. Histopathological examination demonstrated a tumor composed of spindle to oval cells proliferating in a myxoid stroma with a plexiform growth pattern, prominent capillary vascular, and involving the muscularis propria. Immunohistochemical staining showed that the tumor cells were positive for SMA and negative for CD117, DOG1, CD34, S100, and Desmin. The morphologic and immunophenotypic findings were consistent with plexiform fibromyxoma of the stomach. This is a rare pathological entity with clinical and radiologic features that may mimic other gastric mesenchymal tumors, particularly GIST. Conclusion: Through this case, we emphasize the important role of histopathology and immunohistochemistry in the definitive diagnosis, differential diagnosis, and appropriate management of gastric mesenchymal tumors.